PENGARUH PEMBELAJARAN FIQIH TERHADAP PELAKSANAAN IBADAH SHALAT PADA SISWA PROGRAM KHUSUS KELAS PERSIAPAN MADRASAH MUALLIMIN MUALLIMAT TAMBAKBERAS JOMBANG - Mohammad Saat Ibnu Waqfin (Universitas KH. A. Wahab Hasbullah, 2019)
ABSTRACT The Mualimin Mualimat Bahrul Ulum (MMA BU) Tambakberas preparation class is a class that prepares students who wish to enter MMA BU Tambakberas, but they do not yet have the competence to attend KBM, due to difficult subject matter. Therefore these students must enter the preparatory class. Most prep class students come from elementary school or families who have minimal religious knowledge. In preparatory classes they are educated intensively so that they have within one year the basic competencies and content standards set by the madrasa. With such a background, the researcher is interested in researching, that is, with students who have a background that cannot read Arabic writing, fiqh knowledge is lacking, is it effective learning of jurisprudence in the madrasa. Is there any influence of jurisprudence learning on the implementation of prayer on these students. The purpose of this study was to determine the implementation of jurisprudence learning in the class of mualimin nausea preparation and its effect on the implementation of fardlu prayer for special students of MMA BU preparation classes